Public Expenditure, Energy Consumption and Economic Growth in Tunisia During the Period of COVID-19: Comparative Study Between Cartographic Spatial Distribution Analysis and Empirical Validation - MTIRAOUI, Abderraouf; OBEID, Hassan (Technium Sustainability, 2023)
The objective of this article is to study the relationship between public expenditure, energy consumption and economic growth during the period of COVID-19 while highlighting a comparative study between the cartographic spatial distribution analysis and empirical validation. In this framework, we tried to present in a spatial distribution mapping for the case of Tunisia while showing the allocation and distribution of public expenditure between several necessary headings such as basic social items and energy consumption during the period from 1990 to 2018.